2019
DOI: 10.1590/1516-4446-2017-0015
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol presents an inverted U-shaped dose-response curve in a simulated public speaking test

Abstract: Objective:Cannabidiol (CBD), one of the non-psychotomimetic compounds of Cannabis sativa, causes anxiolytic-like effects in animals, with typical bell-shaped dose-response curves. No study, however, has investigated whether increasing doses of this drug would also cause similar curves in humans. The objective of this study was to compare the acute effects of different doses of CBD and placebo in healthy volunteers performing a simulated public speaking test (SPST), a well-tested anxiety-inducing method.Method:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
107
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 185 publications
(130 citation statements)
references
References 41 publications
(64 reference statements)
11
107
1
2
Order By: Relevance
“…Zuardi and his colleagues used a test that simulates speaking in public to show that pretreatment with a single dose of CBD can reduce the associated discomfort in people with social anxiety disorder 11 . A similar effect has been observed in healthy people in anxiety-inducing situations 12 , and several researchers are exploring CBD as a means of soothing social stress in people with autism spectrum disorder. Devinsky notes that many of his patients with epilepsy have also been diagnosed with autism spectrum disorder, and he is involved in two clinical trials that aim to test whether CBD can meaningfully reduce the irritability and anxiety of those with autism.…”
Section: Multitasking Moleculesupporting
confidence: 56%
“…Zuardi and his colleagues used a test that simulates speaking in public to show that pretreatment with a single dose of CBD can reduce the associated discomfort in people with social anxiety disorder 11 . A similar effect has been observed in healthy people in anxiety-inducing situations 12 , and several researchers are exploring CBD as a means of soothing social stress in people with autism spectrum disorder. Devinsky notes that many of his patients with epilepsy have also been diagnosed with autism spectrum disorder, and he is involved in two clinical trials that aim to test whether CBD can meaningfully reduce the irritability and anxiety of those with autism.…”
Section: Multitasking Moleculesupporting
confidence: 56%
“…The anxiolytic effects of CBD are described in the literature. 13,17,18 The TGA has published a series of clinical guidance documents that summarise the available evidence for medicinal cannabis products in chronic pain, palliative care, epilepsy, spasticity in multiple sclerosis and chemotherapy-induced nausea and vomiting. However, definitive evidence in support of specific medicinal cannabis products for various conditions is often not available.…”
Section: Conditions Treatedmentioning
confidence: 99%
“…For example, some effects of CBD seem to have an inverted U-shaped dose–response curve. Regarding anxiety, while a dose superior to 20 mg/kg appears to be ineffective in animals (Guimarhes et al, 1990), a human study with a Simulating Public Speaking Test confirmed this U-shaped dose–response, with an efficacy observed with 300 mg of CBD, but not with 150 mg or 900 mg (Linares et al, 2016). However, other animal studies found an anxiolytic effect with repetitive doses of 30 mg/kg, which may activate different pathways (Campos et al, 2013; Fogaça et al, 2018).…”
Section: Discussionmentioning
confidence: 99%